FEATURES OF FORMATION, CLINICAL CURRENT AND PREVENTIVE MAINTENANCE GLAUCOME IN CONDITIONS SHARPLY CONTONENTAL OF A CLIMATE - Akhmedov , Nozimbek; Mamasoliev , Zoxidjon; Mamatkhujaeva , Gulnaraxan (Medical science of Uzbekistan, 2023)
As a result of carried out(spent) prospektive of clinico-meteorological research was shown, that climateweather - мeteofactors in themselves, irrespective of other risk factors, are connected to frequency glaucome (GK). Is proved, that the greatest number of cases GK and its(her) adverse, heavy current is observed at high levels " of the meteorological factors I-го about " and them the daily allowance fluctuations in the party of increase and decrease(reduction). The various measures on preventive maintenance GK should provide liquidation (easing) of influence мeteofactors and correction caused by them dizadaptive of infringements.